"I'm Just a Girl": Girlhood as a Queer Digital Subject Position. - Doermann, Hannah (Girlhood Studies)
I examine the current rise of social media trends that feature the term "girl," such as the "I'm just a girl" trend. I read these trends as theorizing "girl" as a digital subject position that social media users of various embodied age-based and gendered identities can claim. On social media, "girl" functions as an embrace of the playful, flexible, and communal strands of femininity associated with girlhood that is distinct from the binary gender role of womanhood as well as postfeminist imaginations of girlhood. This theorization of girlhood allows us to understand girlhood as a site for gender transformation and queer identificatory possibilities that can challenge binary models of gender, childhood and adulthood, and symbolic and embodied identities.